Localization of I-BAR domain proteins in invasive cancer cells - Sepponen, Kirsi (2011)
An important step in cancer metastasis is the ability of the cancer cells to degrade the surrounding extracellular matrix (ECM) and migrate through it. To accomplish this, invasive cancer cells generate protrusive structures called invadopodia, which are dynamic cell protrusions that secrete matrix metalloproteinases (MMPs) responsible for the degradation of the ECM.